ANALISIS KEBUTUHAN JARINGAN DISTRIBUSI 20 KV UNTUK MEMENUHI PELANGGAN INDUSTRI BARU 15 MW KAWASAN RANDU GARUT - Hasna Rahma Tazkia (Universitas Diponegoro, 2022)
GI Randu Garut has two transformers with a capacity of 2 x 60 MVA and has 14 existing feeders. PT. PLN UP3 Semarang received a new customer application for the industrial area on Jl. Mt. Kelir Raya 56, Karanganyar, Kec. Monument, Semarang City, Central Java. Installation of customer power is carried out in stages, at an initial stage of 15 MW. Analysis of the need for a 20 kV distribution network is needed to meet the customer's power demand. Meeting the demand for connecting new customers with a power of 15 MW requires supplies from 2 feeders, namely RDT09, an existing feeder with a length of 2430 meters, and building a new feeder RDT16 with a length of 2,419 meters. The RDT09 and RDT16 feeders will be supplied by transformer 2 GI Randu Garut. 15 MW is charged to transformer 2 resulting in transformer 2 capacity will change from 55.5% to 83.3%. After adding 15 MW of load, the voltage drop at the feeder end of RDT 09 is 1.20% and RDT 16 is 1.05%. The voltage drop on the existing 14 feeders is at a value of 0.20% to 5.38%. The voltage drop value still meets the SPLN 72 standard in 1987, which is below +5% and -10%. The power loss of the Randu garut GI after adding 15 MW of load to 1,208.9 kW or 1.56%.